Hubungan Perilaku dengan Kejadian Diabetes Melitus Tipe 2 di Puskesmas Kota Ende Tahun 2021 - Francelina Ivanty Sao Da; Yuliana Radja Riwu; Honey Ivon Ndoen (Yayasan Literasi Sains Indonesia, 2023)
Diabetes mellitus is a serious and chronic (prolonged) disease that causes metabolic intrusion and obstruction, indicated by high blood sugar beyond the normal level. Unhealthy lifestyles, such as smoking, drinking alcohol, bad dietary habit and obesity, lacking of physical activities, and stress, are some of the main contributors or causes of diabetes mellitus. The purpose of this research is to find the direct connection and relation between the behaviour or lifestyle and the case of Diabetes Mellitus Type 2 at Ende City Health Center. The design of this research is a survey analytic research using a case-control approach. The total sample in this research is 86 respondents, with a 1:1 (one-to-one) comparison. The sampling technique used in this study is simple random sampling. The data is taken by doing a guided interview with a questionnaire for test statistic chi-square and odd ratio value. The result of this research shows that the variable of dietary habit (p-value = 0,017 < 0,05 and OR = 3,168 (1,309 – 7,665 and 95% CI), physical activities (p-value = 0,028 < 0,05 and OR = 2,971 (1,212 – 7,279 and 95% CI), consumption of alcohol (p-value = 0,023 < 0,05 and OR = 3,285 (1,273 – 8,478 and 95% CI) directly connected with the case of Diabetes Mellitus Type 2. The variable of knowledge (p-value = 0,829 > 0,05 and OR = 1,206 (0,516 – 2,816 and 95% CI) does not have any connection with the case of Diabetes Mellitus Type 2. Suggestion for the healthcare workers in the Ende City Health Center to always improve and maintain good service of the health care and for the people to have regular check-ups and to develop healthy lifestyle such as having proper dietary habits, doing physical activities and controlling the consumption of alcohol to control the level of blood sugar.